Physical activity level of ambulatory stroke patients: Is it related to neuropsychological factors? - Ersöz Hüseyinsinoğlu, Burcu; Kuran Aslan, Göksen; Tarakçı, Devrim; Razak Özdinçler, Arzu; Küçükoğlu, Hayriye; Baybaş, Sevim (AVES, 2017)
Introduction: Physical inactivity is an important risk factor for stroke and stroke recurrence. There is insufficient knowledge about the physical activity (PA) level in stroke patients who are ambulatory in the subacute phase. Our aim was to compare the PA level between ambulatory stroke patients and a population of the same age and to investigate neuropsychological factors that could affect the PA level in the same stroke group. Methods: Eighty-five subacute stroke patients and 58 healthy subjects were included. Patients' demographic features, disease-related features, and comorbidities were recorded. The PA level was assessed by the International Physical Activity Questionnaire-Short Version and a pedometer (OMRON Walking style II). The Apathy Rating Scale was applied to determine the apathy level. Depression level was investigated by the Geriatric Depression Scale. The standardized Mini-mental State Examination was performed to assess the cognitive status. Results: The PA level was significantly higher in the healthy group than in the stroke group (p< 0.001). Step count and walking distance were significantly higher in healthy group (p= 0.001 and p= 0.04, respectively). The PA level of men was significantly higher than that of women (p= 0.03). Participants who were classified as level 4 had a lower PA level than those who were classified as level 5 according to the Functional Ambulation Category. There was no relationship between the PA level and the apathy, cognitive, and depression levels in the stroke patients (p> 0.05). Conclusion: Subacute stroke patients have a lower PA level than healthy subjects. This is not related to neuropsychological factors. The reasons for minor deficits related to ambulation should be researched further while developing strategies for increasing the PA level of subacute stroke patients.

Amaç: Fiziksel inaktivite inme ve inmenin tekrarında önemli bir risk faktörüdür. İnmenin subakut döneminde ambulatuar olan inmeli hastaların fiziksel aktivite (FA) düzeyi hakkında yetersiz bilgi bulunmaktadır. Çalışmamızın amacı ambulatuar inmeli hastalar ile aynı yaş grubundaki sağlıklı bireylerin FA düzeylerini karşılaştırmak ve aynı inme grubunda FA düzeyini etkileyebilecek nöropsikolojik faktörleri incelemektir. Yöntem: Çalışmaya 85 subakut dönem inmeli hasta ile 58 sağlıklı olgu dahil edilmiştir. Hastaların demografik, hastalık ile ilgili özellikleri ve komorbidite bilgileri kaydedildi. Fiziksel aktivite düzeyi “Uluslararası Fiziksel Aktivite Sorgulaması- Kısa Form” ve pedometre (OMRON Walking style II) ile değerlendirildi. Apati düzeyi “Apati Değerlendirme Skalası” ile ölçüldü. Depresyon düzeyi “Geriatrik Depresyon Skalası”; kognitif durum ise “Standardize Mini Mental Durum Değerlendirmesi” ölçeği ile belirlendi. Bulgular: Sağlıklı olguların FA seviyesi inmeli hastalarla kıyaslandığında sağlıklı olgularda daha yüksek bulundu (p<0,001). Adım sayısı ve yürüme mesafesi de sağlıklı grupta daha yüksekti (sırasıyla; p=0,001; p=0,04). Erkeklerin FA seviyesi kadın hastalara oranla daha yüksek bulundu (p=0,03). Fonksiyonel Ambulasyon Kategorisine göre 4.seviye hastaların FA düzeyi 5. seviye hastalara kıyasla daha düşük bulundu. FA seviyesi ile apati, kognisyon ve depresyon düzeyi arasında anlamlı ilişki yoktu (p>0,05). Sonuç: Subakut dönem inmeli hastaların FA seviyesi sağlıklı olgulardan daha düşüktü. Bu durumun nöropsikolojik faktörlerle ilişkisi yoktu. Subakut inmeli hastaların FA düzeyini yükseltmek için geliştirilecek stratejiler içinde ambulasyon ile ilgili minor defisitler de gözönünde bulundurulmalıdır.
Ambulatuar inmeli hastalarda fiziksel aktivite düzeyi: Nöropsikolojik faktörlerin etkisi var mı?
WOS: 000404296300011
PubMed ID: 28680314
Keywords: Stroke; Apathy; Depression; Cognition; Physical Activity; İnme; Apati; Depresyon; Kognisyon; Fiziksel Aktivite